2017
DOI: 10.1021/acs.jpcc.7b04937
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Oxygen Behavior in the Degradation of Li2MnO3 Cathode Material

Abstract: The Li2MnO3 cathode material is vulnerable to complex degradation behaviors during the operation of battery although it has attracted much attention recently due to its potentially large capacity. In this study, we comprehensively examined the degradation process in Li2MnO3, using theoretical density functional computations as well as experimental techniques (in situ X-ray absorption near edge structure spectroscopy, X-ray diffraction, and Raman spectroscopy). Our study reveals that during the delithiation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The phase compositions of the samples were confirmed by Rietveld refinement of PXRD data ( Figures S1–S3 , the details of the refinement are given in SI) using the values of Ni:Mn ratio for each phase obtained by EDX. The structure of the layered monoclinic phase Li 1+ x M 1− x O 2 can be described as a derivative of the Li 2 MnO 3 structure formed by an alternation of the Li 3 and Li 1− x M 2+ x layers (M = Mn, Ni) along the c axis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 35 ]. The phase composition used in the refinement corresponds to the formula of Li(Li 0.28 Mn 0.64 Ni 0.08 )O 2 (it can also be written as Li 1.92 Mn 0.96 Ni 0.12 O 3 , so the composition is close enough to the Li 2 MnO 3 monoclinic phase).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase compositions of the samples were confirmed by Rietveld refinement of PXRD data ( Figures S1–S3 , the details of the refinement are given in SI) using the values of Ni:Mn ratio for each phase obtained by EDX. The structure of the layered monoclinic phase Li 1+ x M 1− x O 2 can be described as a derivative of the Li 2 MnO 3 structure formed by an alternation of the Li 3 and Li 1− x M 2+ x layers (M = Mn, Ni) along the c axis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 35 ]. The phase composition used in the refinement corresponds to the formula of Li(Li 0.28 Mn 0.64 Ni 0.08 )O 2 (it can also be written as Li 1.92 Mn 0.96 Ni 0.12 O 3 , so the composition is close enough to the Li 2 MnO 3 monoclinic phase).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that pure Li 2 MnO 3 was considered to be electrochemically inactive for a long time, before demonstration of reversible Li + extraction/insertion after “activation” at ~4.5–4.7 V vs. Li/Li + in highly dispersed powder [ 6 ]. Unlike the LiMO 2 layered oxides (M—transition metal), Li 2 MnO 3 (also represented as Li[Li 1/3 Mn 2/3 ]O 2 ) exhibits oxygen anion redox activity that has been confirmed by a number of experimental and computational studies [ 7 , 8 , 9 ]. Single-phase Li 2 MnO 3 suffers from poor cycling stability, low Coulombic efficiency, voltage fading, etc.…”
Section: Introductionmentioning
confidence: 95%
“…Unfortunately, lack of electrolytes with wide voltage windows greatly limits the development of high-voltage LIBs. Therefore, most research works focused on the development of novel electrode materials with high reversible capacity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [18] showed that theoretically Li extraction can be charge compensated by the formation of O 2 from O 2− ions in the lattice. Cho et al [19] demonstrated that oxygen loss is energetically favourable during delithiation. Electrochemical performance was recently examined by doping Al on the Mn site, and it was shown that Al-doped Li 2 MnO 3 exhibits an enhancement on the rate capability and cycling stability [20].…”
Section: Introductionmentioning
confidence: 99%